The Response of Botanical Seeds of Trisula and Biru Lancor Shallot Varieties to Coconut Water Treatment - Sudaryono, Tri (Graduate School, Universitas Brawijaya, 2019)
The use of botanical seeds for seedling cultivation has problems related to the number of produced tubers, where in general botanical seeds on average only produce 1-2 tubers. Another problem with the cultivation of shallots with botanical seeds as a source of seedlings is the low growth of seeds (germination). To overcome the problems that exist in botanical seeds, growth regulators are used. This study aimed to determine the effect of coconut water treatment on the growth and yield of Trisula and Biru Lancor shallot varieties from botanical seeds, carried out from April to August 2018 in Pelem Village in Pare Sub-District, Kediri Regency. The utilized method is soaking the shallot botanical seeds for 4 hours before sowing; the seeds were then sown and planted for a month before being moved to the field. After growing in the field, observations were carried out at 1-week intervals on vegetative and generative growth. Sampling was random, and data was analyzed with t-test/LSD at a level of 5%. The results showed that the botanical seeds of Trisula and Biru Lancor shallot varieties showed different responses to the treatment with young coconut water. The use of coconut water for the Trisula variety led to 70% of plants yielding more than six cloves, while the Biru Lancor variety only had 46.67%. The use of coconut water for the Trisula variety yielded a fresh tuber weight of 71.2 g per plant at harvest; if converted per hectare, the Trisula variety can yield approximately 32 tons of fresh tubers. Meanwhile, the Biru Lancor variety yielded a tuber weight of 57.4 g per plant at harvest, and if converted per hectare, the Biru Lancor variety can yield approximately 26 tons of fresh tubers.Keywords: Botanical seed, Coconut Water, Shallots